Changes in identity in Alice Munro’s stories: a sociopsychological analysis - Danytė, Milda (Literatūra, 2015)
Alice Munro’s winning of the 2013 Nobel Prize for literature was a surprise only in the sense that no one who writes only short stories has ever won it before. Otherwise, among writers and literary specialists she has long been considered a leading candidate, as she is one of the masters of this complex literary genre, known especially for her probing into the small-town communities of the southern part of the province of Ontario. This is an Anglo-Celtic (English, Scottish, and Irish) society which formed through waves of immigration from the early 19th century as a farmland interspersed with small towns. These apparently dull communities are, as Munro reveals, rich in subtle class distinctions and spoken and unspoken social norms of behavior. Munro has explained how she only gradually understood the richness of the material that her home country had given her, “full of events and emotions and amazing things going on all the time”.